2008
DOI: 10.1097/meg.0b013e32830edb15
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection upregulates interleukin-18 production from gastric epithelial cells

Abstract: Background Helicobacter pylori infection induces a biased T helper type 1 (Th1) response that produces IFN-γ and Fas ligand (FasL). Th1 cytokines are associated with apoptosis in the gastric epithelial cells. Aim We aimed to define the role of the recently cloned IL-18, a IFN-γ inducing factor, in gastric mucosal injury induced by H. pylori infection. Methods Twenty-seven gastric ulcer (GU) patients and 20 functional dyspepsia (FD) patients were enrolled in this study. Mucosal biopsy samples were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…Later, Hitzler et al (240) showed in both cultured DCs and in vivo that H. pylori infection activates caspase-1, leading to IL-1β/IL-18 processing and secretion. Consistently, three studies, using human GC cell lines, gastric tissue, and murine models, confirmed increased expression of caspase-1, IL-1β, and IL-18 in H. pylori -infected cells (171, 241, 242). Further, Jiang et al (243), also using a murine model, have reported the expression of NLRP3 inflammasome-related molecules as well as serum IL-1β, IL-18, and IL-33 levels to be significantly increased in H. pylori -infected mice.…”
Section: Nod-like Receptors and Helicobacter Pylori-related Gastric Csupporting
confidence: 61%
“…Later, Hitzler et al (240) showed in both cultured DCs and in vivo that H. pylori infection activates caspase-1, leading to IL-1β/IL-18 processing and secretion. Consistently, three studies, using human GC cell lines, gastric tissue, and murine models, confirmed increased expression of caspase-1, IL-1β, and IL-18 in H. pylori -infected cells (171, 241, 242). Further, Jiang et al (243), also using a murine model, have reported the expression of NLRP3 inflammasome-related molecules as well as serum IL-1β, IL-18, and IL-33 levels to be significantly increased in H. pylori -infected mice.…”
Section: Nod-like Receptors and Helicobacter Pylori-related Gastric Csupporting
confidence: 61%
“…IFNγ is produced within the H. pylori infected gastric mucosa (40), and previously we showed a synergistic effect of IFNγ and H. pylori on B7-H1 upregulation on GEC (18). Thus, we examined whether IFNγ could modulate H. pylori -mediated B7-H2 downregulation on GECs.…”
Section: Resultsmentioning
confidence: 94%
“…We found a marked increase in B7-H1 expression on the surface of the AGS cells 24 h after infection with an HP strain (Fig 2). Because interferon-γ (IFN-γ) can be produced within the HP-infected gastric mucosa [23], which might also stimulate B7-H1 expression [24], we investigated whether IFN-γ could modulate HP-mediated B7-H1 expression in AGS cells. We found that the IFN-γ treatment also markedly stimulated B7-H1 expression in AGS cells (Fig 2).…”
Section: Resultsmentioning
confidence: 99%